Geochemistry and origin of natural gas in the petroliferous Mahu sag, northwestern Junggar Basin, NW China: Carboniferous marine and Permian lacustrine gas systems. (October 2016) - Tao, Keyu; Cao, Jian; Wang, Yuce; Ma, Wanyun; Xiang, Baoli; Ren, Jianglin; Zhou, Ni
Highlights: The Mahu sag of NW Junggar Basin is prospective for natural gas exploration. Both sapropelic- and humic-type gases occur in the region. Source rocks include Carboniferous and Permian mudstones. Deep anticlines hosting both kerogen- and oil-cracking gases are favorable targets. Abstract: The Mahu sag, located in the northwestern Junggar Basin of NW China, is a renowned Carboniferous marine–Permian lacustrine hydrocarbon depocenter that in theory could host both oil and gas. However, as ongoing hydrocarbon exploration and production are focused solely on oil, few gas prospects have been discovered. In this paper, we discuss the possible occurrence of natural gas deposits, based on a comprehensive study of gas geochemistry, including gas composition, carbon isotopes and compositions of light hydrocarbons (C5 –C7 ), and biomarkers in retrograde condensates, combined with geological information available for the study area. Our results indicate that three types of natural gas occur in the region: a sapropelic-type gas derived from the lower Permian Fengcheng Formation (P1 f ), a humic-type gas sourced from Carboniferous strata (C) and the overlying lower Permian Jiamuhe Formation (P1 j ), and a humic-type gas derived from the middle Permian Lower Wuerhe Formation (P2 w ). The P1 f -sourced sapropelic-type gas accumulated during at least two distinct periods of time, yielding low maturity oil-associated gases and mature to high-maturity kerogen/oil-cracking gases. The Carboniferous and P1 j -sourced humic-type gases are mainly high-maturity to over-mature kerogen/oil-cracking gases, without obvious geochemical evidence for a multi-stage accumulation. The P2 w -sourced gas is a mature humic-type gas. Of these three types of gas, the former two have the potential to form significant gas deposits and constitute valid exploration targets, making the Mahu sag a prospective area for gas exploration. Favorable areas for gas occurrence include deep anticlines hosting both kerogen- and oil-cracking gases. The inferred exploration targets occur at significant depths, which is why little drilling has been undertaken in these areas and major gas discoveries have yet to be made.